Kesenjangan Model Pendidikan Karakter Lokal Berbasis Nilai Belom Bahadat dan Belum Penyang Hinje Simpei - Endah Sucia Dewi; Noormuslim; Muslimah (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to examine the gaps in the development of local character education models based on the values of Belom Bahadat and Belum Penyang Hinje Simpei and to identify their potential contributions to character education in Indonesia. The study employs a qualitative approach using a library research design. Data were collected from scholarly books, peer-reviewed journal articles, and relevant previous studies on character education, Dayak local wisdom, and the philosophical foundations of Belom Bahadat and Belum Penyang Hinje Simpei. Data analysis followed the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. The findings indicate that these values embody religious, moral, social, and multicultural principles that are highly relevant as a foundation for character education. However, existing studies remain largely descriptive and normative, lacking applicative curriculum designs and empirical evaluations of implementation. This study underscores the need to develop a more systematic, contextual, and measurable local character education model to effectively integrate Dayak cultural values into formal education